Transversus Abdominal Plane Block in Children: Efficacy and Safety. (June 2019) - Sola, Chrystelle; Menacé, Cecilia; Bringuier, Sophie; Saour, Anne-Charlotte; Raux, Olivier; Mathieu, Olivier; Capdevila, Xavier; Dadure, Christophe
Abstract : BACKGROUND: The transversus abdominis plane (TAP) block has become a common regional anesthesia technique for pain management in a wide variety of abdominal procedures. Evidence to support any particular local anesthetic regimen as well as pharmacokinetic and systemic toxicity risks of TAP block remain insufficiently studied in children. The aim of this study was to compare the analgesic effects and investigate pharmacokinetic profile of levobupivacaine after ultrasound-guided TAP block using a low volume/high concentration (LVHC) or a high volume/low concentration (HVLC) solution in children. METHODS: This prospective randomized study included children scheduled for day-case inguinal surgery. Children were randomized to receive TAP block using 0.4 mg·kg −1 levobupivacaine as either HVLC (0.2 mL·kg −1 of 0.2% levobupivacaine) or LVHC (0.1 mL·kg −1 of 0.4% levobupivacaine). The primary outcome was the number of children who required opioid rescue analgesia postoperatively. Pharmacokinetic profile study of levobupivacaine was also performed. RESULTS: Seventy patients were equally randomized, and 65 were included in the final analysis. Seventy-one percent of patients did not require any postoperative opioid analgesia. The number of patients who received rescue analgesia was 12 (35%) in the LVHC group and 7 (23%) in the HVLC group (relative risk, 0.64; 95% confidence interval [CI], 0.29–1.42; P = .26). Mean pain scores (FLACC [faces, legs, activity, cry, and consolability]) at postanesthesia care unit discharge did not differ between LVHC and HVLC groups, respectively, 0.39 ± 0.86 and 1 ± 1.71 with mean group difference −0.60 (95% CI, −1.27 to 0.06; P = .08). The pharmacokinetic profile of levobupivacaine was comparable in the 2 groups: the mean total and free levobupivacaine peak concentrations were 379 ± 248 and 3.95 ± 3.16 ng·mL −1, respectively, occurring 22.5 ± 11 minutes after injection. The highest total and free levobupivacaine concentrations collected, respectively, 1360 and 15.1 ng·mL −1, remained far below theoretical toxic thresholds. CONCLUSIONS: In children, quality of postoperative pain control provided by TAP block using levobupivacaine 0.4 mg·kg −1 administered as either HVLC or LVHC did not differ and was associated with a very low risk of local anesthetic systemic toxicity.